Directions of automation of technological processes in the agricultural complex of Ukraine - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Skliar, Radmila; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Podashevskaya, H. (My University, 2020)
EN: The article outlines the directions of automation of technological processes in the agro-industrial complex of Ukraine. RU: В статье обозначены направления автоматизации технологических процессов в агропромышленном комплексе Украины.
Keywords: agro-industrial complex; technological process; automation; агропромышленный комплекс; технологический процесс; автоматизация